PENGARUH KUALITAS KEHIDUPAN KERJA (QWL) DAN PENGHARGAAN TERHADAP PRODUKTIVITAS GURU SD NEGERI DI KECAMATAN KEBON JERUK JAKARTA BARAT - Maria Ari Muryadi (Universitas Negeri Jakarta, 2018)
A study of determining the influence of QWL and reward on the teachers productivity at state elementary school has been done which the samples were taken in district kebon jeruk west jakarta city. In this work a survey method with path analysis techniques was used by applying a questioner as a researched instrument. 152 responders were involved by sending their feedback within the questioner. Those responders were decided using simple random sampling among all teachers that working at the predetermined location. The results showing both QWL and reward perform significant effect on the teacher’s productivity. Moreover there was a correlation between QWL and reward which one affects the other.